A Practice‐Based Research Database to Study Perinatal Nurse Home Visiting to Pregnant Women With Diabetes. Issue 1 (4th January 2019) - Bloch, Joan R.; McKeever, Amy E.; Zupan, Susan K.; Birati, Yosefa; Chiatti, Beth; Devido, Jessica A.; Maldonado, Linda T.; Geller, Pamela A.; Barkin, Jennifer L.
Abstract: Background and Aims: Accumulation of real‐world evidence from practice‐based perinatal nurse home visits to pregnant women with diabetes prompted this translational perinatal health disparities research. Given the global diabetes epidemic, this academic–community partnered research team is studying the utilization, processes, and outcomes of this understudied model of perinatal nurse home visiting that provide home‐based enhanced diabetes care to pregnant women. Because the nursing records provide the rich source of data for the study, our aim is to provide an in‐depth description of the Philadelphia Pregnancy and Diabetes Home Visiting (PPD‐HV) research database developed from data in the longitudinal nursing records. Methods: This descriptive study uses retrospective data abstracted from paper‐based perinatal nurse home visiting clinical records to create the PPD‐HV, a HIPAA compliant, secure REDCap electronic research database. The sample includes 248 urban, pregnant women with diabetes who received a total of 1, 644 home visits during the year 2012. The setting was Philadelphia, a large metropolitan city in the northeastern part of the United States. The PPD‐HV database followed the information fields of the paper‐based clinical nursing forms, which were originally designed by following the Omaha System to guide documenting the nursing process used in caring for patients in their homes. Results: Using REDCap, the PPD‐HV research database is robust with 239 variables and captures longitudinal clinical nursing data. Among the pregnant women with diabetes receiving nurse home visits, the mean age was 30.7 years, most were single, and had given birth to other children. Linking Evidence to Action: Real‐world clinical nursing practice data provide a rich source of research data to advance understandings about this model of enhanced diabetes care and the pregnant women with diabetes receiving the care. Considering the global epidemic of diabetes, this is a perinatal nurse home visiting model to replicate and evaluate.